Speciation of Selenium in Supplements by High Performance Liquid Chromatography-Inductively Coupled Plasma-Mass Spectrometry - Bakirdere, Sezgin; Volkan, Muervet; Ataman, O. Yavuz (TAYLOR & FRANCIS INC, 2015)
Anion and cation exchange high-performance liquid chromatography (HPLC) combined with inductively coupled plasma-mass spectrometry (ICP-MS) were used for speciation of selenium in supplements. All the parameters in the extraction, separation, and determination procedures were optimized. Recovery studies for the selenium species from the anion and cation exchange columns were performed and there were no analyte losses. Limits of detection for selenium(IV), selenium(VI), Se in selenomethionine, and Se in selenocystine were 0.85, 0.68, 0.84, and 0.99 nanogram per milliliter, respectively. Six brands were analyzed to identify and quantify the selenium species present, and the results found were compared with the values given on the labels. The selenium species matched the labeled species for four brands, whereas two brands were found to contain inorganic Se(VI) in contrast with the labeled claim of selenomethionine.
Keywords: HPLC-ICP-MS; Vitamin; Selenium; Speciation; Inductively coupled plasma-mass spectrometry; High-performance liquid chromatography; CLOUD POINT EXTRACTION; INORGANIC SELENIUM; ORBITRAP MS; HUMAN URINE; HEALTH; PRECONCENTRATION; ENVIRONMENT; SAMPLES; CANCER; Chemistry